Feeding pattern of children under two years in some selected villages (Bangladesh Journal of Medical Science, 2010)
Objective: The present study was aimed to find out the feeding pattern of children less than two years of age in rural areas. Methodology: The study area consisting of three villages of Muradnagar Upazila under the district of Comilla. Families having children under-two years of age were included in the study. A total number of 54 families finally entered in the study. Respondents were interviewed using structured questionnaire regarding initiation of breast feeding of the new born, their breast feeding pattern and weaning of the children. Socio-demographic characteristics of the respondents were recorded. Data were presented as number and percentage. Results: Out of the 54 respondents 52 (96.3%) were mothers and 2 (3.7%) fathers. Of the total 50 (92.6%) respondents was housewife. Among 54 respondents 36 (66.7%) were in the age group of 18 to 25 years. Thirteen (24.1%) respondents were illiterate and among the rest 27 (50%) had primary level and 2 (3.7%) had bachelor level of education. Twenty six (48.1%) respondents said newborns were given breast milk first and rest 28 (51.9%) mentioned about giving of honey, cow's milk and sweet water made of sugar or sugar product. Twelve (22.2%) mothers started breast feeding within 15 minutes after birth, 28 (51.9%) after 1 hour or more. Twenty one 21 (38.9%) had given exclusive breast feeding to the children for six months and 33 (61.1%) given additional stuff during that time. Thirty (55.6%) mothers started weaning before reaching 6 months of age, 13 (24.0%) between 6 months to 12 months and 1 (1.9%) started after 12 months. Commonly used weaning foods were rice, shuzi, khichuri, cow's milk, infant formula, fish, egg, meat, honey, vegetables and fruits especially banana. Conclusion: The data suggest wide range of variability still exists in allowing colostrums to the newborn, breast feeding itself and also weaning practice. Key Words: Feeding pattern; weaning; children. DOI: 10.3329/bjms.v8i4.4709 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp110-117